2018
DOI: 10.1121/1.5048181
|View full text |Cite
|
Sign up to set email alerts
|

One-way sound propagation via spatio-temporal modulation of magnetorheological fluid

Abstract: This manuscript details the possibility of achieving one-way sound propagation using a smart fluid such as magnetorheological fluid (MRF) by subjecting it to a spatio-temporally varying magnetic field. The local speed of sound in MRF is dependent on applied magnetic field as demonstrated in several experimental works and this property of MRF has been leveraged, in this work, to induce one-way bandgaps. Initially, a general wave equation pertaining to fluid with space-and-time-varying material properties was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In a later publication by the same authors, they observed significant differences in the propagation depending on the orientation and mode of application of the magnetic field. 227 Nanda and Karami 228 detailed the possibility of achieving one-way sound propagation using MRFs by subjecting them to a time-space varying magnetic field.…”
Section: Applicationsmentioning
confidence: 99%
“…In a later publication by the same authors, they observed significant differences in the propagation depending on the orientation and mode of application of the magnetic field. 227 Nanda and Karami 228 detailed the possibility of achieving one-way sound propagation using MRFs by subjecting them to a time-space varying magnetic field.…”
Section: Applicationsmentioning
confidence: 99%
“…Topological insulators have been shown to break sound propagation reciprocity 20,21 but these techniques provide narrow band solutions which are not applicable to three-dimensional waves. Materials with time modulated properties support non-reciprocal broadband sound, however, the modulation must occur on a significant length scale, therefore these materials necessarily occupy a large volume which becomes an issue especially at low frequencies [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…The repulsive force between the magnets reduces the natural frequency of the beam and makes the vibration system nonlinear and, therefore, less sensitive to the frequency of excitation. Using magnetic forces for tuning and manipulation of mechanical dynamical systems (Nanda and Karami, 2018;Nanda, 2018, Nanda et al, 2016 has a long and storied history. A schematic diagram of a nonlinear harvester is shown in Figure 1(b).…”
Section: Nonlinear Energy Harvestersmentioning
confidence: 99%